Assessment of CMIP6 Cloud Fraction and Comparison with Satellite Observations. Issue 2 (3rd February 2020) - Vignesh, P. Preetham; Jiang, Jonathan H.; Kishore, P.; Su, Hui; Smay, Timothy; Brighton, Nicholas; Velicogna, Isabella
Abstract: The seasonal and regional variations of cloud fractions are compared across two generations of global climate model ensembles, specifically, the Coupled Model Intercomparison Project‐5 (CMIP5) and CMIP6, through the historical period in terms of skills and multimodel agreement. We find a wider spread of historical cloud fraction changes in the CMIP6 than was simulated by the CMIP5. The global mean cloud fractions of CMIP6 increased by about 4.5% from the CMIP5, which attributed to greater changes in the northern hemisphere than in the southern hemisphere. The CMIP6 cloud fractions in recent years are validated with the CALIPSO_CLOUSAT observations to understand the cloud fraction uncertainties in CMIP6 models. The CMIP6 ensemble mean of cloud fractions compares well with the observations with a mean difference of 0.5% in lower altitudes. The CMIP6 cloud fractions are higher than the observations at higher latitudes in both hemispheres in the upper troposphere, and the biases vary from one model to another. The spatial difference between the ensemble and observations is further revealed over the tropics: where the model displays a 3% higher bias. In addition, we observed a significant trend occuring in the northern hemisphere since the mid‐20th century using calculations of cloud fraction trends based on the robust regression technique. Finally, we reduce the differences between the model and observations by applying a simple regression technique. The results exemplify that the model and modified observations compare well, with the root mean square value decreased by nearly 28%, and the correlation increased significantly. Key Points: The seasonal and regional variations of cloud fraction are compared across two generations of global climate model ensembles: CMIP6 and CMIP5 The CMIP6 cloud fractions in recent years are validated with the CALIPSO_CLOUSAT observations The differences between the model and the observations are reduced by applying the simple regression technique